The effectiveness of the procedures followed by the organizers during the Hajj season on the safety of the elderly in Al-Mashaer train area - Alsulimani, Lina Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
The aim of this study is to identify the authorities responsible for organizing the Hajj season which focus on the most important needs of the elderly in Al-Mashaer train area, and to measure the quality of services provided to elderly people in Al-Mashaer train area, and the most prominent international standards for safety at train stations in Britain - Japan – Australia - America. In addition, the qualitative approach that serves the objectives of the study was used, and the data collection tool represented in the research questionnaire consisting of two parts was also utilized. A special section for the beneficiaries targeting the elderly who had previously performed the Hajj, knowing the obstacles they faced in the train area, and measuring the perceived quality of services from their point of view, and the sample consisted of 61elderly people, and another questionnaire targeted the organizers in Al-Mashaer train area to measure the perceived quality of services from their point of view. The sample was composed of 106 people who participated in organizing the Hajj season in Al-Mashaer train area. The 19-paragraph for elderly people and 21-paragraph for organizers in Al-Mashaer train area. questionnaire was published using the Servequal Service Quality Measurement Model, which consists of five dimensions: tangibility, reliability, responsiveness, safety and emotion. The study concluded with the following most prominent results: That the elements of tangible service and service in terms of reliability in Al- Mashaer train area for providing service to the elderly are widely available, and one of the most important things that shows is the ease of use of elevators in the train area, and the existence of special tracks for elderly vehicles. However, there is a need to develop, improve and increase the number of toilets in the area, while the elderly people are mostly satisfied with the services provided to them. Moreover, there is a need to review and support the emergency plan to achieve the safety and security required for the elderly. The results also revealed that most of the elderly sample agreed that the workers care about them personally, and that there are no statistically significant differences about the quality of services provided at Al-Mashaer to the beneficiaries due to the difference in gender among the elderly people. This indicates that there is a consensus among pilgrims, of different sex, on the level of service provided.
Keywords: Hajj and Umrah; the elderly; security and safety; services; service elements